Environmental Health Risk Analysis of SO2 and NO2 in Kemiri Muka Village, Depok City, Indonesia - Aulia, Nuansa Dwika; Hartono, Budi (UI Scholars Hub, 2024)
Kemiri Muka is a village in Beji Subdistrict, Depok City, Indonesia. Based on a preliminary survey conducted in one of the neighborhood units of Kemiri Muka Village, the residential had a high density of houses and was close to traditional markets, toll roads, the main road of Depok City, and landfills. This caused the air quality in the village area to decline. This study aimed to analyze risks to public health and the environment from exposure to toxic substances, SO2 and NO2, which are high in the air due to transportation on the highway and population density. The sample from this study consisted of three age groups: 15 adults, 3 school-age children, and 5 toddlers. This study used the Environmental Health Risk Analysis to analyze the data. Based on the results, the risk quotient (RQ) of non-carcinogenic effects by exposure to inhalation of chemical agents, NO2 and SO2, were also included in safe risk because all RQ values were